Processing and fabrication of advanced materials XIII : (Stallion Press, 2005)
The two volumes contain the technical papers presented at the XIII international symposium entitled "Processing and Fabrication of Advanced Materials," held in Singapore in 2004. This was the 13th in a series of symposia bringing together engineers and researchers from the industry, academia and national laboratories, working on aspects related to the processing, fabrication and characterization of advanced materials, to present and discuss their latest findings.